A CuS@NiCo-LDHs hollow nano-octahedral heterojunction electrocatalyst and its preparation and application
By constructing CuS@NiCo-LDHs hollow nanooctahedral heterojunction electro-catalyst, the existing OER catalysts have poor activity, poor stability and slow kinetics in alkaline electrolytes, and high activity, stability and low cost catalytic performance have been achieved.
Patent Information
- Application Number
- CN202410581249.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-05-11
AI Technical Summary
Existing OER catalysts have problems such as poor activity, poor stability, high cost and slow kinetics in alkaline electrolytes.
By using Cu2O nanooctahedral as a hard template to undergo a precipitation conversion reaction with soluble sulfide, the CuS shell was grown, and the Cu2O core was etched by inorganic strong acid to obtain CuS hollow nanooctahedral. Then a layer of NiCo-LDHs nanosheets were heterogeneously grown on its surface to construct CuS@NiCo-LDHs hollow nanooctahedral heterojunction electrocatalyst.
It improves the intrinsic activity and stability of the catalyst, reduces the reaction energy barrier, enhances electron mobility, provides a rich heterogeneous interface, improves mass transfer efficiency and active site exposure, and solves the problems of poor activity, poor stability and slow kinetics of existing catalysts.
Smart Images

Figure CN119101940B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts for oxygen evolution by electrolysis of water, and in particular to a CuS@NiCo-LDHs hollow nano octahedron heterojunction catalyst and a preparation method and application thereof. Background Art
[0002] At present, the development of hydrogen energy is an effective way to solve the resource crisis and environmental pollution. Water electrolysis is considered to be the most efficient and environmentally friendly hydrogen production technology. It consists of two half reactions: hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Compared with the reduction process of cathode HER, the four-electron transfer process of anode OER usually exhibits relatively slow kinetics, so efficient catalysts are needed to improve energy conversion efficiency and reduce energy consumption. Precious metal oxides (RuO2, IrO2) are considered to be the most advanced electrocatalysts in alkaline media. However, the high cost, scarcity and poor stability of precious metals limit their widespread application. Therefore, it is urgent to explore and construct highly active non-precious metal electrocatalysts with good prospects. Transition metal compounds have become an ideal substitute for precious metal catalysts in alkaline media. Although transition metal compound electrocatalysts have made some progress in the field of water electrolysis, it is still a huge challenge to explore electrocatalysts with high activity, low cost and good stability in alkaline media.
[0003] In the process of optimizing and modifying non-precious metal catalysts, various strategies such as defect engineering, heterogeneous doping and interface engineering are used to regulate the electronic structure and coordination environment of non-precious metal catalysts to improve their catalytic performance. Among them, the construction of heterojunctions through interface engineering plays an important role in improving the performance of OER catalysts. However, when constructing heterostructures, there are still major obstacles in the selection of suitable materials and the construction of efficient interface active sites. Nickel-cobalt layered double hydroxide nanosheets (NiCo-LDHs) have attracted increasing attention due to their advantages such as simple preparation, flexible structure, adjustable electronic structure and induced surface modification. However, layered double hydroxides have low conductivity, insufficient active sites and poor stability in alkaline electrolytes. Constructing heterostructures, regulating directional electron transfer through strong interface coupling, and increasing real active sites are effective measures to improve their OER catalytic performance. How to use layered double hydroxides to construct heterostructures and obtain high-performance catalysts is a difficult problem that technicians in this field need to solve. Summary of the invention
[0004] The purpose of the present invention is to provide a CuS@NiCo-LDHs hollow nano-octahedral heterojunction catalyst and its preparation and application, so as to solve the problems of poor activity, poor stability, high cost and slow kinetics faced by the existing OER catalysts in alkaline electrolytes in the above-mentioned prior art.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention: a method for preparing a CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalyst, comprising the following steps:
[0007] The Cu2O nano-octahedron is used as a hard template to undergo a precipitation conversion reaction with a soluble sulfide, and a CuS shell layer is grown on the surface of the Cu2O nano-octahedron to obtain a Cu2O@CuS nano-octahedron core-shell structure intermediate; the Cu2O@CuS nano-octahedron core-shell structure intermediate is etched by an inorganic strong acid to remove the Cu2O core to obtain a CuS hollow nano-octahedron; and a layer of NiCo-LDHs nanosheets is heterogeneously grown on the surface of the CuS hollow nano-octahedron to obtain the CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalyst.
[0008] Furthermore, the specific method of using Cu2O nano-octahedron as a hard template to react with soluble sulfide for precipitation conversion reaction includes:
[0009] Soluble sulfide is added to the Cu2O nano-octahedron suspension, and the mixture is stirred to perform a precipitation conversion reaction. After the reaction is completed, the mixture is washed and dried to obtain the Cu2O@CuS nano-octahedron core-shell structure intermediate.
[0010] Cu2O nano-octahedron not only serves as a hard template for the reaction, but also as a precursor for preparing the Cu2O@CuS nano-octahedron core-shell structure intermediate. During the precipitation conversion reaction, a layer of CuS crystallizes, grows, and precipitates on the surface of the Cu2O nano-octahedron to form a Cu2O@CuS core-shell structure intermediate.
[0011] Furthermore, the soluble sulfide is sodium sulfide or potassium sulfide; the mass ratio of the Cu2O nano-octahedron contained in the Cu2O nano-octahedron suspension to the added soluble sulfide is 1.6-3.0:0.3-0.6; and the time of the precipitation conversion reaction is 20-40 minutes.
[0012] Furthermore, the soluble sulfide is added in the form of a solution.
[0013] Furthermore, the specific method of etching the Cu2O@CuS nano-octahedral core-shell structure intermediate using an inorganic strong acid includes:
[0014] The Cu2O@CuS nano octahedron core-shell structure intermediate is added into the mixed solvent 1 to obtain the Cu2O@CuS nano octahedron core-shell structure intermediate suspension; an inorganic strong acid is added into the Cu2O@CuS nano octahedron core-shell structure intermediate suspension, and the mixture is etched by stirring. After the etching is completed, the mixture is washed and dried to obtain the CuS hollow nano octahedron.
[0015] Furthermore, the inorganic strong acid is hydrochloric acid, nitric acid or sulfuric acid; the mass ratio of the Cu2O@CuS nano-octahedral core-shell structure intermediate contained in the Cu2O@CuS nano-octahedral core-shell structure intermediate suspension to the added inorganic strong acid is 1:7 to 14. The inorganic strong acid is added in the form of a solution, and the mass of the inorganic strong acid described here refers to the mass of the solute in the inorganic strong acid solution.
[0016] Furthermore, the mixed solvent 1 is formed by mixing water and ethanol (referring to anhydrous ethanol) in a volume ratio of 1:0.5-1.5; and the etching time is 3-8 minutes.
[0017] Furthermore, the specific method of heterogeneously growing a layer of NiCo-LDHs nanosheets on the surface of the CuS hollow nano-octahedron includes:
[0018] The CuS hollow nano-octahedron is added into a mixed solvent 2 to obtain a CuS hollow nano-octahedron suspension; Ni salt, Co salt and surfactant are added into the CuS hollow nano-octahedron suspension, and organic amine and organic sodium salt are added after stirring evenly (the purpose of adding organic amine and organic sodium salt is to adjust the morphology and size with the help of organic compounds), and the mixture is stirred evenly again and heated to react, and after the reaction is completed, the mixture is washed and dried to obtain the CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalyst.
[0019] Furthermore, the Ni salt is nickel sulfate, nickel nitrate or nickel chloride; the Co salt is cobalt sulfate, cobalt nitrate or cobalt chloride; the surfactant is polyvinyl pyrrolidone; the organic amine is hexamethylenetetramine; the organic sodium salt is trisodium citrate; the mass ratio of the CuS hollow nano-octahedron contained in the CuS hollow nano-octahedron suspension to the added Ni salt, Co salt, surfactant, organic amine and organic sodium salt is 0.5-1: 0.058-0.582: 0.116-1.164: 4-10: 0.7-1.4: 0.129-0.296; the reaction temperature is 80-100°C, and the reaction time is 4-7h.
[0020] Furthermore, the mixed solvent 2 is formed by mixing water and ethanol (referring to anhydrous ethanol) in a volume ratio of 1:0.25-0.5; the CuS hollow nano-octahedron is added to the mixed solvent 2 and ultrasonically dispersed for 20-40 minutes to obtain the CuS hollow nano-octahedron suspension; the stirring time after adding Ni salt, Co salt and surfactant is 5-10 minutes; the stirring time after adding organic amine and organic sodium salt is 10-20 minutes.
[0021] Furthermore, the preparation method of the Cu2O nano-octahedron comprises:
[0022] A surfactant, a precipitant and a reducing agent are sequentially added to an inorganic copper salt solution, and the solution is allowed to stand for aging reaction. After the reaction is completed, the solution is washed and dried to obtain the Cu2O nano-octahedron.
[0023] Furthermore, the inorganic copper salt solution is a copper chloride solution, a copper sulfate solution or a copper nitrate solution; the surfactant is polyvinyl pyrrolidone (PVP); the precipitant is a strong base; the reducing agent is L-ascorbic acid; the mass ratio of the inorganic salt contained in the inorganic copper salt solution to the added surfactant, precipitant and reducing agent is 1.71-3.42:55.56-111.12:8-16:8.45-16.90; the temperature of the static aging reaction is 70-100°C, and the time is 4-6h.
[0024] Furthermore, the strong base is strong sodium oxide, and the strong sodium oxide is added in the form of a solution; the L-ascorbic acid is added in the form of a solution.
[0025] The second technical solution of the present invention: a CuS@NiCo-LDHs hollow nano-octahedral heterojunction electrocatalyst prepared according to the above preparation method.
[0026] The CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalyst of the present invention inherits the octahedron shape of the Cu2O sacrificial template, and at the same time, CuS has a hollow structure due to the etching of Cu2O, and the surface of the CuS hollow nano-octahedron is covered with a large number of ultra-thin nanosheet arrays, so that the CuS@NiCo-LDHs heterojunction electrocatalyst presents a hollow octahedron structure with nanosheets on the surface.
[0027] Furthermore, the side length of the CuS@NiCo-LDHs hollow nano-octahedron is 0.8-1.2 μm.
[0028] The third technical solution of the present invention: an application of the above-mentioned CuS@NiCo-LDHs hollow nano-octahedral heterojunction electrocatalyst in oxygen evolution in alkaline water electrolysis.
[0029] Furthermore, the alkaline electrolyte used in the alkaline electrolysis of water for oxygen evolution is a potassium hydroxide solution or a sodium hydroxide solution, and the concentration of the alkaline electrolyte is 1 mol / L and the pH is 14.
[0030] Furthermore, the CuS@NiCo-LDHs hollow nano-octahedral heterojunction electrocatalyst exerts its effect by being loaded on a working electrode; the substrate of the working electrode is a glassy carbon electrode.
[0031] The present invention discloses the following technical effects:
[0032] 1. The present invention heterogeneously grows a highly active NiCo-LDHs nanosheet array on a CuS nano-octahedron with excellent conductivity, designs and constructs a CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalyst, constructs a rich heterojunction interface through interface engineering, uses the interface coupling effect to induce directional electron transfer, reduces the reaction barrier, and enhances the OER catalytic performance. The preparation method of the present invention has the advantages of simple synthesis process, abundant and easy to obtain raw materials, low cost, short cycle time, time-saving and energy-saving, and environmental protection and cleanliness. The CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalyst prepared by this method has the advantages of novel morphology, rich active sites, high catalytic activity, good stability, etc., and solves the problems of poor activity of OER electrocatalysts, low electron transmission capacity, poor stability, and slow kinetics.
[0033] 2. The preparation method of the present invention has universal applicability. By simply adjusting the reaction time and the ratio of raw materials, a series of CuS@NiCo-LDHs hollow nano-octahedral heterojunction electrocatalysts with similar morphology and structure can be obtained.
[0034] 3. Compared with the existing OER electrocatalysts, the CuS@NiCo-LDHs hollow nano-octahedral heterojunction electrocatalyst prepared in the present invention has the following advantages:
[0035] (1) The strong coupling effect of the heterostructure induces the directional transfer of electrons from NiCo-LDHs to CuS, generating a large number of high-valent Ni and Co active sites, which significantly improves the intrinsic activity of the electrocatalyst. At the same time, by adjusting the energy band center, the electrophilicity of the Ni and Co active sites is enhanced, the reaction of -OH and ·OH in the electrolyte to generate ·O is promoted, and the RDS (Rate-determining step) reaction energy barrier is reduced;
[0036] (2) The introduction of CuS components regulates the electronic state density at the Fermi level of CuS@NiCo-LDHs, reduces the band gap, and enhances the electron mobility;
[0037] (3) The special morphology (heterogeneous morphology) provides a rich heterogeneous interface, which is conducive to full contact with the electrolyte, thereby improving the mass transfer efficiency and exposing more active sites. At the same time, NiCo-LDHs nanosheets are decorated on the octahedral shell surface of CuS, avoiding the agglomeration and collapse of NiCo-LDHs, giving it excellent stability and a more uniform charge distribution, reducing the electron transfer resistance between the reactants and improving the electron transfer efficiency.
[0038] In summary, the preparation method proposed in the present invention has a simple preparation process, mild generation conditions, low reaction cost, safe and controllable, clean and environmentally friendly, and the obtained product has a novel morphology and uniform size, which can be used for large-scale preparation of OER electrocatalysts. Through this preparation method, a series of CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalysts with novel morphology, unique composition, high activity and good stability can be obtained. The heterogeneous interface synergistic coupling increases the active sites, promotes charge transfer, enhances the bonding effect with oxygen-containing intermediates, improves the adsorption capacity, reduces the reaction barrier, and improves the OER electrocatalytic performance. The present invention solves the problems of expensive prices, scarce quantities, complex preparation processes, and limited stability of existing commercial precious metal catalysts. The prepared CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalyst can be used for alkaline electrocatalytic oxygen evolution reaction, which is of great significance to the development of water electrolysis hydrogen production technology, and has important research value and broad application prospects for solving resource crises and environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0040] Figure 1 Schematic diagram of the synthesis of the CuS@NiCo-LDHs hollow nano-octahedral heterojunction electrocatalyst in Example 1;
[0041] Figure 2 The XRD pattern of the Cu2O nano-octahedron prepared in step (1) of Example 1;
[0042] Figure 3 This is a SEM image of the Cu2O nano-octahedron obtained in step (1) of Example 1;
[0043] Figure 4 The XRD spectrum of the Cu2O@CuS core-shell structure intermediate prepared in step (2) of Example 1;
[0044] Figure 5 This is a SEM image of the Cu2O@CuS core-shell structure intermediate obtained in step (2) of Example 1;
[0045] Figure 6 The XRD pattern of the CuS hollow nano-octahedron prepared in step (3) of Example 1;
[0046] Figure 7 This is a SEM image of the CuS hollow nano-octahedron obtained in step (3) of Example 1;
[0047] Figure 8 The XRD spectrum of the CuS@NiCo-LDHs hollow nano-octahedral heterojunction electrocatalyst prepared in step (4) of Example 1;
[0048] Fig. 9 This is a SEM image of the CuS@NiCo-LDHs hollow nano-octahedral heterojunction electrocatalyst prepared in step (4) of Example 1;
[0049] Fig.10 TEM image of the CuS@NiCo-LDHs hollow nano-octahedral heterojunction electrocatalyst prepared in step (4) of Example 1;
[0050] Fig.11 This is the EDS spectrum of the CuS@NiCo-LDHs hollow nano-octahedral heterojunction electrocatalyst prepared in step (4) of Example 1, wherein the inset is a table of the atomic percentage and mass percentage of each element;
[0051] Fig.12 The XRD spectrum of the CuS@NiCo-LDHs-4h hollow nano-octahedral heterojunction electrocatalyst finally prepared in Example 2;
[0052] Fig.13 This is a SEM image of the CuS@NiCo-LDHs-4h hollow nano-octahedral heterojunction electrocatalyst finally prepared in Example 2;
[0053] Fig.14 The XRD spectrum of the CuS@NiCo-LDHs-(0.01) hollow nano-octahedron heterojunction electrocatalyst finally prepared in Example 3;
[0054] Fig.15 This is a SEM image of the CuS@NiCo-LDHs-(0.01) hollow nano-octahedron heterojunction electrocatalyst finally prepared in Example 3;
[0055] Fig.16 The XRD spectrum of the NiCo-LDHs nanosheet electrocatalyst prepared in Comparative Example 2;
[0056] Fig.17 This is a SEM image of the NiCo-LDHs nanosheet electrocatalyst prepared in Comparative Example 2;
[0057] Fig.18 The XRD pattern of the commercial RuO2 powder of Comparative Example 3;
[0058] Fig.19 XRD spectrum of the CuS@NiCo-LDHs(4) hollow nano-octahedral electrocatalyst prepared in Comparative Example 4;
[0059] Fig. 20 This is a SEM image of the CuS@NiCo-LDHs(4) hollow nano-octahedral electrocatalyst prepared in Comparative Example 4;
[0060] Fig.21 XRD pattern of the Cu2O-cube nanocube prepared in step (1) of comparative example 5;
[0061] Fig. 22 This is a SEM image of the Cu2O-cube nanocube prepared in step (1) of Comparative Example 5;
[0062] Fig.23 The XRD spectrum of the Cu2O@CuS-cube core-shell structure intermediate prepared in step (2) of Comparative Example 5;
[0063] Fig.24 XRD pattern of the CuS-cube hollow nanocube prepared in step (3) of comparative example 5;
[0064] Fig.25 XRD spectrum of the CuS@NiCo-LDHs-cube hollow nanocube heterojunction electrocatalyst prepared in step (4) of Comparative Example 5;
[0065] Fig.26 This is a SEM image of the CuS@NiCo-LDHs-cube hollow nanocube heterojunction electrocatalyst prepared in step (4) of Comparative Example 5;
[0066] Fig. 27 The linear scanning curves of the electrocatalysts of Examples 1-3 and Comparative Examples 1-5 in alkaline electrolyte, with a scanning range of 1.024V to 1.924V;
[0067] Fig.28 Tafel curves of the electrocatalysts of Examples 1-3 and Comparative Examples 1-5 in alkaline electrolyte;
[0068] Fig.29CV curves of the electrocatalysts of Examples 1-3 and Comparative Examples 1-5 in a non-Faraday voltage range (0.35V to 0.45V vs. Hg / HgO) in an alkaline electrolyte;
[0069] Fig.30 is the double-layer capacitance (C dl ) curve graph;
[0070] Fig.31 The electrochemical impedance spectroscopy (EIS) curves of the electrocatalysts of Examples 1-3 and Comparative Examples 1-5 in alkaline electrolytes are shown;
[0071] Fig.32 It is a constant current stability curve diagram of the electrocatalysts of Examples 1-3 and Comparative Examples 1-5 in alkaline electrolyte. DETAILED DESCRIPTION
[0072] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0073] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0074] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0075] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0076] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0077] The present invention provides a method for preparing a CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalyst, comprising the following steps:
[0078] The Cu2O nano-octahedron is used as a hard template to undergo a precipitation conversion reaction with a soluble sulfide, and a CuS shell layer is grown on the surface of the Cu2O nano-octahedron to obtain a Cu2O@CuS nano-octahedron core-shell structure intermediate; the Cu2O@CuS nano-octahedron core-shell structure intermediate is etched by an inorganic strong acid to remove the Cu2O core to obtain a CuS hollow nano-octahedron; and a layer of NiCo-LDHs nanosheets is heterogeneously grown on the surface of the CuS hollow nano-octahedron to obtain the CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalyst.
[0079] Furthermore, the specific method of using Cu2O nano-octahedron as a hard template to react with soluble sulfide for precipitation conversion reaction includes:
[0080] Soluble sulfide is added to the Cu2O nano-octahedron suspension, and the mixture is stirred to perform a precipitation conversion reaction. After the reaction is completed, the mixture is washed and dried to obtain the Cu2O@CuS nano-octahedron core-shell structure intermediate.
[0081] Furthermore, the specific method of etching the Cu2O@CuS nano-octahedral core-shell structure intermediate using an inorganic strong acid includes:
[0082] The Cu2O@CuS nano octahedron core-shell structure intermediate is added into the mixed solvent 1 to obtain the Cu2O@CuS nano octahedron core-shell structure intermediate suspension; an inorganic strong acid is added into the Cu2O@CuS nano octahedron core-shell structure intermediate suspension, and the mixture is etched by stirring. After the etching is completed, the mixture is washed and dried to obtain the CuS hollow nano octahedron.
[0083] Furthermore, the specific method of heterogeneously growing a layer of NiCo-LDHs nanosheets on the surface of the CuS hollow nano-octahedron includes:
[0084] The CuS hollow nano-octahedron is added into a mixed solvent 2 to obtain a CuS hollow nano-octahedron suspension; Ni salt, Co salt and surfactant are added into the CuS hollow nano-octahedron suspension, and organic amine and organic sodium salt are added after stirring evenly (the purpose of adding organic amine and organic sodium salt is to adjust the morphology and size with the help of organic compounds), and the mixture is stirred evenly again and heated to react, and after the reaction is completed, the mixture is washed and dried to obtain the CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalyst.
[0085] Furthermore, the preparation method of the Cu2O nano-octahedron comprises:
[0086] A surfactant, a precipitant and a reducing agent are sequentially added to an inorganic copper salt solution, and the solution is allowed to stand for aging reaction. After the reaction is completed, the solution is washed and dried to obtain the Cu2O nano-octahedron.
[0087] That is, the preparation method of the CuS@NiCo-LDHs hollow nano-octahedral heterojunction electrocatalyst provided by the present invention specifically comprises the following steps:
[0088] (1) preparing Cu2O nano-octahedrons: adding a surfactant, a precipitant and a reducing agent to an inorganic copper salt solution in sequence, allowing the solution to stand for an aging reaction, and washing and drying the solution after the reaction to obtain the Cu2O nano-octahedrons;
[0089] (2) Preparing a Cu2O@CuS core-shell structure intermediate: adding a soluble sulfide to a Cu2O nano-octahedron suspension, stirring to carry out a precipitation conversion reaction, washing and drying after the reaction is completed to obtain the Cu2O@CuS nano-octahedron core-shell structure intermediate; the Cu2O nano-octahedron suspension is prepared by mixing Cu2O nano-octahedrons and water;
[0090] (3) Preparing CuS hollow nano-octahedrons: adding the Cu2O@CuS nano-octahedron core-shell structure intermediate to the mixed solvent 1 to obtain a Cu2O@CuS nano-octahedron core-shell structure intermediate suspension; adding an inorganic strong acid to the Cu2O@CuS nano-octahedron core-shell structure intermediate suspension, stirring and etching, washing and drying after the etching is completed to obtain the CuS hollow nano-octahedrons;
[0091] (4) Preparation of CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalyst: adding the CuS hollow nano-octahedron into mixed solvent 2 to obtain a CuS hollow nano-octahedron suspension; adding Ni salt, Co salt and surfactant to the CuS hollow nano-octahedron suspension, stirring evenly, then adding organic amine and organic sodium salt, stirring evenly again and heating to react, washing and drying after the reaction is completed to obtain the CuS@NiCo-LDHs heterojunction electrocatalyst hollow nano-octahedron.
[0092] As a preferred embodiment of the present invention, the inorganic copper salt solution in step (1) is a copper chloride solution, a copper sulfate solution or a copper nitrate solution; the surfactant is polyvinyl pyrrolidone; the precipitant is a strong base; the reducing agent is L-ascorbic acid; the mass ratio of the inorganic salt contained in the inorganic copper salt solution to the added surfactant, precipitant and reducing agent is 1.71-3.42:55.56-111.12:8-16:8.45-16.90; the temperature of the static aging reaction is 70-100°C, and the time is 4-6h.
[0093] The strong base is strong sodium oxide, which is added in the form of a solution; and the L-ascorbic acid is added in the form of a solution.
[0094] As a preferred embodiment of the present invention, the soluble sulfide in step (2) is sodium sulfide or potassium sulfide; the mass ratio of the Cu2O nano-octahedron contained in the Cu2O nano-octahedron suspension to the added soluble sulfide is 1.6-3.0:0.3-0.6; and the time of the precipitation conversion reaction is 20-40 min.
[0095] The soluble sulfide is added in the form of a solution.
[0096] As a preferred embodiment of the present invention, the inorganic strong acid in step (3) is hydrochloric acid, nitric acid or sulfuric acid; the mass ratio of the Cu2O@CuS nano octahedral core-shell structure intermediate contained in the Cu2O@CuS nano octahedral core-shell structure intermediate suspension to the added inorganic strong acid is 1:7 to 14.
[0097] The mixed solvent 1 is formed by mixing water and ethanol in a volume ratio of 1:0.5-1.5; the etching time is 3-8 minutes.
[0098] As a preferred embodiment of the present invention, the Ni salt in step (4) is nickel sulfate, nickel nitrate or nickel chloride; the Co salt is cobalt sulfate, cobalt nitrate or cobalt chloride; the surfactant is polyvinyl pyrrolidone; the organic amine is hexamethylenetetramine; the organic sodium salt is trisodium citrate; the mass ratio of the CuS hollow nano-octahedron contained in the CuS hollow nano-octahedron suspension to the added Ni salt, Co salt, surfactant, organic amine and organic sodium salt is 0.5-1: 0.058-0.582: 0.116-1.164: 4-10: 0.7-1.4: 0.129-0.296; the reaction temperature is 80-100°C, and the reaction time is 4-7h.
[0099] The mixed solvent 2 is formed by mixing water and ethanol in a volume ratio of 1:0.25-0.5; the CuS hollow nano-octahedron is added to the mixed solvent 2 and then ultrasonically dispersed for 20-40 minutes to obtain the CuS hollow nano-octahedron suspension; the stirring time after adding Ni salt, Co salt and surfactant is 5-10 minutes; the stirring time after adding organic amine and organic sodium salt is 10-20 minutes.
[0100] As a preferred embodiment of the present invention, the washing in steps (1)-(4) is centrifugal washing, the rotation speed of the centrifugal washing is 6000-10000 rpm, and the time of each centrifugal washing is 6-10 minutes; the temperature of the drying is 50-80°C, and the time is 10-24 hours.
[0101] The present invention also provides a CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalyst prepared according to the preparation method.
[0102] The present invention also provides an application of the CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalyst in oxygen evolution by alkaline water electrolysis.
[0103] The preparation method and application of the CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalyst of the present invention are further described below in conjunction with specific embodiments.
[0104] Unless otherwise specified, the materials used in the following examples were prepared according to existing methods or directly purchased from the market.
[0105] The room temperature or normal temperature involved in the following examples refers to 20-25°C.
[0106] Example 1
[0107] 1. Preparation of a CuS@NiCo-LDHs hollow nano-octahedral heterojunction electrocatalyst. The synthesis diagram is shown in Figure 1As shown, the specific steps are as follows:
[0108] (1) Preparation of Cu2O nano-octahedrons: 0.171 g of CuCl2·2H2O was added to a round-bottom flask containing 100 mL of deionized water under an oil bath at 80°C to obtain a CuCl2 solution; 5.556 g of PVP was added under stirring, and then 15 mL of 2 mol / L NaOH solution (containing 1.2 g of NaOH) was added to the solution, and stirred for 30 minutes. Finally, 10 mL of 0.6 mol / L L-ascorbic acid solution (containing 1.06 g of L-ascorbic acid) was added dropwise to the mixed solution. Stirring was stopped after 5 minutes, and the mixture was allowed to stand for aging reaction at 80°C for 4 hours. After the reaction was completed, the mixture was washed three times by alternating centrifugation with deionized water and anhydrous ethanol at a speed of 8000 rpm, each time for 8 minutes. The obtained product was then placed in a 60°C oven to dry for 12 hours, and finally the product was fully ground to obtain Cu2O nano-octahedrons.
[0109] (2) Preparation of Cu2O@CuS core-shell structure intermediate: 60 mL of deionized water was added to a beaker at room temperature and placed on a magnetic stirrer, and then 100 mg of Cu2O nano-octahedral powder was added thereto and stirred to disperse evenly to obtain a Cu2O nano-octahedral suspension; then 40 mL of 6.25 mmol / L Na2S solution (containing 19.6 mg of Na2S) was added to the Cu2O nano-octahedral suspension under stirring conditions, and stirred for precipitation conversion reaction for 30 minutes. After the reaction was completed, deionized water and anhydrous ethanol were used for alternating centrifugation washing three times at a speed of 10,000 rpm, each centrifugation time was 8 minutes, and then the obtained product was placed in a 60°C oven to dry for 12 hours. After sufficient grinding, a Cu2O@CuS core-shell structure intermediate was obtained.
[0110] (3) Preparation of CuS hollow nano-octahedrons: 500 mg of Cu2O@CuS core-shell structure intermediate powder was placed in a beaker containing a mixed solvent (referred to as mixed solvent 1) consisting of 40 mL of deionized water and 40 mL of anhydrous ethanol at room temperature, and stirred and evenly dispersed on a magnetic stirrer to obtain a Cu2O@CuS nano-octahedron core-shell structure intermediate suspension; then 30 mL of 6 mol / L HCl solution (containing 6.56 g of HCl) was added to the Cu2O@CuS nano-octahedron core-shell structure intermediate suspension under stirring conditions, and the etching reaction was carried out for 5 minutes. After the reaction was completed, the mixture was washed three times by alternating centrifugation with deionized water and anhydrous ethanol at a speed of 6000 rpm, each centrifugation time was 5 minutes, and then the obtained product was placed in a 60°C oven to dry for 12 hours, and finally the product was fully ground to obtain CuS hollow nano-octahedrons.
[0111] (4) Preparation of CuS@NiCo-LDHs hollow nano-octahedrons: 50 mg of CuS hollow nano-octahedron powder was added to a round-bottom flask containing a mixed solvent consisting of 40 mL of deionized water and 10 mL of anhydrous ethanol (referred to as mixed solvent 2), and ultrasonicated for 30 minutes to uniformly disperse it to obtain a CuS hollow nano-octahedron suspension; 0.1 mmol (29.1 mg) of Ni(NO3)2·6H2O, 0.2 mmol (58.2 mg) of Co(NO3)2·6H2O and 1 g of PVP were added to the CuS hollow nano-octahedron suspension, and then placed on a magnetic stirrer and stirred for 5 minutes, 0.5 mmol (70.1 mg) of hexamethylenetetramine and 0.05 mmol (12.9 mg) of trisodium citrate were added, and stirred for 10 minutes. Finally, the mixed suspension was placed in a 90°C oil bath and stirred for 6 hours. After the reaction was completed, deionized water and anhydrous ethanol were used for alternating centrifugal washing three times at a speed of 8000 rpm, each centrifugation time was 8 minutes, and then the obtained product was placed in a 60°C oven to dry for 12 hours. Finally, the product was fully ground to obtain the CuS@NiCo-LDHs hollow nano-octahedral heterojunction electrocatalyst.
[0112] Figure 2 This is the XRD spectrum of the Cu2O nano-octahedron prepared in step (1) of Example 1. Its diffraction peak matches well with the standard card (05-0667) of Cu2O, indicating that the Cu2O nano-octahedron precursor is successfully synthesized.
[0113] Figure 3 This is the SEM image of the Cu2O nano-octahedron prepared in step (1) of Example 1. It can be seen that the Cu2O prepared according to the above method has a regular nano-octahedron morphology, and has a smooth surface, uniform size and regular morphology.
[0114] Figure 4 The XRD spectrum of the Cu2O@CuS core-shell structure intermediate obtained in step (2) of Example 1 has obvious diffraction peaks that are basically consistent with the standard card (05-0667) of Cu2O. It can be seen from the figure that the diffraction peak of the precursor Cu2O is weakened, and there are some very weak diffraction peaks, which is because a CuS shell layer is formed on its surface.
[0115] Figure 5 This is the SEM image of the Cu2O@CuS core-shell structure intermediate obtained in step (2) of Example 1. The surface of Cu2O gradually becomes rough. This is because during the reaction process, S ions gradually replace Cu ions on the surface of Cu2O through ion exchange, forming a CuS shell layer on its surface.
[0116] Figure 6This is the XRD spectrum of the CuS hollow nano-octahedron obtained in step (3) of Example 1. Its diffraction peak is basically consistent with the standard card (06-0464) of CuS, indicating that the CuS hollow nano-octahedron is successfully synthesized.
[0117] Figure 7 This is the SEM image of the CuS hollow nano-octahedron obtained in step (3) of Example 1. It can be seen from the figure that the CuS is in the shape of a hollow octahedron, the morphology has not collapsed, and the Cu2O is completely etched.
[0118] Figure 8 This is the XRD spectrum of the CuS@NiCo-LDHs hollow nano-octahedral heterojunction electrocatalyst prepared in step (4) of Example 1. It can be seen from the figure that the target product corresponds to the characteristic peak of the standard card (06-0464) of CuS, and there is no diffraction peak of NiCo-LDHs, indicating that NiCo-LDHs exists in an amorphous form.
[0119] Fig. 9 The SEM image of the CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalyst obtained in step (4) of Example 1 shows that NiCo-LDHs nanosheets are evenly distributed on the surface of the CuS hollow nano-octahedron, and the heterostructure has a large specific surface area, indicating that the CuS@NiCo-LDHs hollow nano-octahedron is successfully obtained, and the side length of the CuS@NiCo-LDHs hollow nano-octahedron is 0.8 to 1.2 μm. In addition, compared with the SEM image of the CuS hollow nano-octahedron obtained in step (3), the surface of the CuS hollow nano-octahedron is relatively flat, indicating that the CuS@NiCo-LDHs hollow nano-octahedron is a heterostructure material with a novel morphology.
[0120] Fig.10 This is a TEM image of the CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalyst prepared in step (4) of Example 1. It can be seen from the figure that CuS@NiCo-LDHs exists in the form of hollow nano-octahedrons and Cu2O is successfully etched.
[0121] Fig.11 This is the EDS spectrum of the CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalyst prepared in step (4) of Example 1, wherein the inset is a table of the atomic percentage and mass percentage of each element. It can be seen from the figure that the CuS@NiCo-LDHs hollow nano-octahedron contains five main elements, Cu, S, Ni, Co, and O, which are uniformly dispersed on the catalyst surface.
[0122] Example 2
[0123] The same as Example 1, except that in step (4), the suspension after adding 0.5 mmol hexamethylenetetramine and 0.05 mmol trisodium citrate is placed in a 90° C. oil bath and stirred for 4 h. The final product is recorded as CuS@NiCo-LDHs-4h hollow nano-octahedron.
[0124] Fig.12 This is the XRD spectrum of the CuS@NiCo-LDHs-4h hollow nano-octahedral heterojunction electrocatalyst finally prepared in Example 2. It can be seen from the figure that the target product corresponds to the characteristic peak of the standard card (06-0464) of CuS, and there is no diffraction peak of NiCo-LDHs, indicating that NiCo-LDHs exists in an amorphous form.
[0125] Fig.13 This is the SEM image of the CuS@NiCo-LDHs-4h hollow nano-octahedron heterojunction electrocatalyst finally prepared in Example 2. It can be seen from the figure that NiCo-LDHs nanosheets are evenly distributed on the surface of the CuS hollow nano-octahedron, and the heterostructure has a large specific surface area, indicating that the CuS@NiCo-LDHs hollow nano-octahedron is successfully obtained, and the side length of the CuS@NiCo-LDHs hollow nano-octahedron is 0.8~1.2μm.
[0126] Example 3
[0127] The same as Example 1, except that the amount of Ni(NO3)2·6H2O added in step (4) is 0.01 mmol (2.91 mg), and the amount of Co(NO3)2·6H2O added is 0.02 mmol (5.82 mg). The final product is recorded as CuS@NiCo-LDHs-(0.01) hollow nano-octahedron.
[0128] Fig.14 This is the XRD spectrum of the CuS@NiCo-LDHs-(0.01) hollow nano-octahedral heterojunction electrocatalyst finally prepared in Example 3. It can be seen from the figure that the target product corresponds to the characteristic peak of the standard card (06-0464) of CuS, and there is no diffraction peak of NiCo-LDHs, indicating that NiCo-LDHs exists in an amorphous form.
[0129] Fig.15This is the SEM image of the CuS@NiCo-LDHs-(0.01) hollow nano-octahedron heterojunction electrocatalyst finally prepared in Example 3. It can be seen from the figure that NiCo-LDHs nanosheets are evenly distributed on the surface of the CuS hollow nano-octahedron, and the heterostructure has a large specific surface area, indicating that the CuS@NiCo-LDHs hollow nano-octahedron is successfully obtained, and the side length of the CuS@NiCo-LDHs hollow nano-octahedron is 0.8~1.2μm.
[0130] Comparative Example 1
[0131] The steps (1) to (3) of Example 1 were used to prepare CuS hollow nano-octahedrons as Comparative Example 1.
[0132] Comparative Example 2
[0133] The preparation steps of NiCo-LDHs nanosheets are as follows:
[0134] Add 100mg Ni(NO3)2·6H2O, 100mg Co(NO3)2·6H2O, 200mg urea and 50mg PVP to a beaker, place the beaker on a magnetic stirrer, add 15mL ethanol and 15mL deionized water to stir and disperse evenly, after stirring, transfer the mixture into a 50mL reactor liner and place it in a 90℃ oven to react for 10h. After the reaction is completed, alternately centrifuge and wash three times at 8000rpm with deionized water and anhydrous ethanol, each centrifugation time is 8 minutes, then place the obtained product in a 60℃ oven to dry for 12h, and finally grind the product thoroughly to obtain NiCo-LDHs nanosheets.
[0135] Fig.16 This is the XRD spectrum of the NiCo-LDHs nanosheet electrocatalyst prepared in Comparative Example 2. It can be seen from the figure that the diffraction peaks of the synthesized NiCo-LDHs nanosheet are basically consistent with the standard card (22-0444) of Ni(OH)2, indicating that the NiCo-LDHs nanosheet has been successfully synthesized.
[0136] Fig.17 This is the SEM image of the NiCo-LDHs nanosheet flower electrocatalyst prepared in Comparative Example 2. It can be seen from the figure that NiCo-LDHs is in the shape of a nanosheet flower.
[0137] Comparative Example 3
[0138] Commercial RuO2 powder (Cas number: 12036-10-1) produced by Shanghai McLean Biochemical Technology Co., Ltd. was purchased as Comparative Example 3.
[0139] Fig.18This is the XRD spectrum of the commercial RuO2 powder of Comparative Example 3. It can be seen from the figure that its diffraction peak matches well with the standard card of RuO2 (43-1027), indicating that it is pure phase RuO2.
[0140] Comparative Example 4
[0141] The same as Example 1, except that in step (4), 0.5 mmol hexamethylenetetramine and 0.05 mmol trisodium citrate were not added, and the CuS hollow nano-octahedron suspension was directly placed in a 90° C. oil bath and stirred for 6 h. The final product was recorded as CuS@NiCo-LDHs(4) hollow nano-octahedron.
[0142] Fig.19 This is the XRD spectrum of the CuS@NiCo-LDHs (4) hollow nano-octahedral electrocatalyst prepared in Comparative Example 4. It can be seen from the figure that its diffraction peak is basically consistent with the standard card (06-0464) of CuS, and the diffraction peak of NiCo-LDHs is not observed.
[0143] Fig. 20 This is the SEM image of the CuS@NiCo-LDHs(4) hollow nano-octahedral electrocatalyst prepared in Comparative Example 4. In the figure, no uniformly sized nanosheets are clearly observed on the octahedral surface, and only some particles are unevenly distributed on the octahedral surface, indicating that organic amines and organic sodium salts can indeed adjust the morphology and size of the nanosheets, making them evenly distributed on the CuS surface to form a heterogeneous structure.
[0144] Comparative Example 5
[0145] Preparation of CuS@NiCo-LDHs-cube hollow nanocubes, the steps are as follows:
[0146] (1) Preparation of Cu2O-cube nanocubes: Under an oil bath at 80°C, 0.171 g of CuCl2·2H2O was added to a round-bottom flask containing 100 mL of deionized water to obtain a CuCl2 solution; 15 mL of 2 mol / L NaOH solution (containing 1.2 g of NaOH) was then added to the solution and stirred for 30 minutes. Finally, 10 mL of 0.6 mol / L L-ascorbic acid solution (containing 1.06 g of L-ascorbic acid) was added dropwise to the mixed solution. Stirring was stopped after 5 minutes and the mixture was allowed to stand for aging reaction at 80°C for 4 hours. After the reaction was completed, the mixture was washed three times by alternating centrifugation with deionized water and anhydrous ethanol at 8000 rpm, each time for 8 minutes. The obtained product was then dried in an oven at 60°C for 12 hours. Finally, the product was fully ground to obtain a Cu2O-cube nanocube.
[0147] (2) Preparation of Cu2O@CuS-cube core-shell structure intermediate: 60 mL of deionized water was added to a beaker at room temperature and placed on a magnetic stirrer, and then 100 mg of Cu2O nanocube powder was added and stirred to disperse evenly to obtain a Cu2O nanocube suspension; then 40 mL of 6.25 mmol / L Na2S solution (containing 19.6 mg of Na2S) was added to the Cu2O nanocube suspension under stirring conditions, and the precipitation conversion reaction was stirred for 30 minutes. After the reaction was completed, deionized water and anhydrous ethanol were used for alternating centrifugation washing three times at a speed of 10,000 rpm, each centrifugation time was 8 minutes, and then the obtained product was placed in a 60°C oven to dry for 12 hours. After sufficient grinding, the Cu2O@CuS-cube core-shell structure intermediate was obtained.
[0148] (3) Preparation of CuS-cube hollow nanocubes: 500 mg of Cu2O@CuS-cube core-shell structure intermediate powder was placed in a beaker containing a mixed solvent (referred to as mixed solvent 3) consisting of 40 mL of deionized water and 40 mL of anhydrous ethanol at room temperature, and stirred and evenly dispersed on a magnetic stirrer to obtain a Cu2O@CuS-cube core-shell structure intermediate suspension; then 30 mL of 6 mol / L HCl solution (containing 6.56 g of HCl) was added to the Cu2O@CuS-cube core-shell structure intermediate suspension under stirring conditions, and the etching reaction was carried out for 5 minutes. After the reaction was completed, the mixture was washed three times by alternating centrifugation with deionized water and anhydrous ethanol at a speed of 6000 rpm, each centrifugation time was 5 minutes, and then the obtained product was placed in a 60°C oven to dry for 12 hours, and finally the product was fully ground to obtain CuS-cube hollow nanocubes.
[0149] (4) Preparation of CuS@NiCo-LDHs-cube hollow nanocubes: 50 mg of CuS hollow nanocube powder was added to a round-bottom flask containing a mixed solvent consisting of 40 mL of deionized water and 10 mL of anhydrous ethanol (referred to as mixed solvent 4), and ultrasonicated for 30 minutes to uniformly disperse it to obtain a CuS hollow nanocube suspension; 0.1 mmol (29.1 mg) of Ni(NO3)2·6H2O and 0.2 mmol (58.2 mg) of Co(NO3)2·6H2O were added to the CuS hollow nanocube suspension, and then placed on a magnetic stirrer and stirred for 5 minutes, 0.5 mmol (70.1 mg) of hexamethylenetetramine and 0.05 mmol (12.9 mg) of trisodium citrate were added, and stirred for 10 minutes. Finally, the mixed suspension was placed in a 90°C oil bath and stirred for 6 hours. After the reaction was completed, deionized water and anhydrous ethanol were used for alternating centrifugal washing three times at a speed of 8000 rpm, each centrifugation time was 8 minutes, and then the obtained product was placed in a 60°C oven to dry for 12 hours. Finally, the product was fully ground and the final product was recorded as CuS@NiCo-LDHs-cube hollow nanocube.
[0150] Fig.21 This is the XRD spectrum of the Cu2O-cube nanocube prepared in step (1) of comparative example 5. Its diffraction peak matches well with the standard card of Cu2O (05-0667), indicating that the Cu2O-cube nanocube precursor is successfully synthesized.
[0151] Fig. 22 This is the SEM image of the Cu2O-cube nanocube prepared in step (1) of comparative example 5. It can be seen that the Cu2O-cube prepared according to the above method has a regular nanocube morphology, a smooth surface, uniform size and a regular morphology.
[0152] Fig.23 This is the XRD spectrum of the Cu2O@CuS-cube core-shell structure intermediate obtained in step (2) of comparative example 5. Its obvious diffraction peaks are basically consistent with the standard card (05-0667) of Cu2O. It can be seen from the figure that the diffraction peaks of the precursor Cu2O-cube are weakened, and there are some very weak diffraction peaks. This is because a CuS-cube shell layer is formed on the surface.
[0153] Fig.24 This is the XRD spectrum of the CuS-cube hollow nanocube prepared in step (3) of Comparative Example 5. Its diffraction peak is basically consistent with the standard card of CuS (06-0464), indicating that the CuS-cube hollow nanocube is successfully synthesized.
[0154] Fig.25This is the XRD spectrum of the CuS@NiCo-LDHs-cube hollow nanocube heterojunction electrocatalyst prepared in step (4) of comparative example 5. It can be seen from the figure that the target product corresponds to the characteristic peak of the standard card (06-0464) of CuS, and there is no diffraction peak of NiCo-LDHs, indicating that NiCo-LDHs may exist in an amorphous form.
[0155] Fig.26 This is an SEM image of the CuS@NiCo-LDHs-cube hollow nanocube heterojunction electrocatalyst prepared in step (4) of comparative example 5. It can be seen from the figure that NiCo-LDHs nanosheets are evenly distributed on the surface of the CuS-cube nanocube, indicating that the CuS@NiCo-LDHs-cube hollow nanocube is successfully obtained, and the side length of the CuS@NiCo-LDHs-cube hollow nanocube is 0.4 to 1.0 μm.
[0156] Performance Test Example 1
[0157] (1) Fabrication of working electrode
[0158] Weigh 4 mg of electrocatalyst, add 250 μL of water and 250 μL of 5wt% Nafion solution, ultrasonicate in an ultrasonic cleaner for 15 minutes to evenly disperse the electrocatalyst to obtain electrocatalyst ink, then use a pipette to transfer 20 μL of electrocatalyst ink and drop it on the polished glassy carbon electrode (GCE, 5 mm diameter) to evenly cover the electrode surface, and dry it naturally at room temperature as a working electrode. Six working electrodes were prepared using the CuS@NiCo-LDHs hollow nano-octahedron of Example 1, the CuS@NiCo-LDHs-4h hollow nano-octahedron of Example 2, the CuS@NiCo-LDHs-(0.01) hollow nano-octahedron of Example 3, the CuS hollow nano-octahedron of Comparative Example 1, the NiCo-LDHs nano-sheet flower of Comparative Example 2, and the RuO2 powder of Comparative Example 3 as electrocatalysts.
[0159] (2) OER performance test of electrocatalysts in alkaline electrolyte
[0160] The electrochemical test was conducted on a CHI760e (Shanghai Chenhua) workstation using a standard three-electrode system. A graphite rod was used as the counter electrode, a Hg / HgO electrode was used as the reference electrode, and the glassy carbon electrode loaded with different electrocatalysts prepared in step (1) of this performance test example was used as the working electrode. The present invention converts all potentials into reversible hydrogen electrodes (RHE), E RHE (V) = E Hg / HgO +0.098+0.059×14. At a scan rate of 5 mV s -1The linear voltammetric curve was tested under the condition of scanning range of 1.024V~1.924V(vs.RHE). The linear voltammetric curve was plotted as a curve of log(j) and overpotential η(V) to obtain the Tafel slope diagram. Electrochemical impedance spectroscopy (EIS) test was carried out according to the open circuit voltage in the frequency range of 100kHz~0.01Hz. In the potential range of 0.35~0.45V(vs.Hg / HgO), 10, 20, 40, 60, 80 and 100mV s -1 CV curve under scanning rate. Plot the half of the absolute sum of current density corresponding to the middle value of CV in the center of the scanning range with the scanning speed. The slope represents the double layer capacitance (C dl ).
[0161] (3) OER stability test of electrocatalyst in alkaline electrolyte
[0162] The electrochemical test was conducted on a CHI760e (Shanghai Chenhua) workstation using a standard three-electrode system. A graphite rod was used as the counter electrode, a Hg / HgO electrode was used as the reference electrode, and the glassy carbon electrode loaded with different electrocatalysts prepared in step (1) of this performance test example was used as the working electrode. The chronopotentiometry was used at 10 mA / cm 2 The OER stability of the catalyst was tested at a current density of .
[0163] Fig. 27 The linear scanning curves of the electrocatalysts of Examples 1-3 and Comparative Examples 1-5 in alkaline electrolyte, the scanning range is 1.024V~1.924V, wherein curve a is Example 1, curve b is Example 2, curve c is Example 3, curve d is Comparative Example 1, curve e is Comparative Example 2, curve f is Comparative Example 3, curve g is Comparative Example 4, and curve h is Comparative Example 5. It can be seen from the figure that the electrocatalysts prepared in Examples 1-3 have good OER catalytic performance, at 20mA / cm 2 At the current density of 1.7 V vs. RHE, the overpotentials are 355 mV, 332 mV and 335 mV respectively; while the electrocatalyst prepared in Comparative Example 4 has the worst OER catalytic performance, and even cannot reach 20 mA / cm at 1.7 V vs. RHE. 2 ; Comparative Example 3 Commercial RuO2 at 20mA / cm 2 At a current density of 20 mA / cm, the overpotential is 334 mV, and the OER catalytic performance is comparable to that of Examples 1-3; the OER catalytic performance of the electrocatalyst prepared in Comparative Example 1 is worse than that of Examples 1-3. 2 The overpotential is 641 mV at a current density of 20 mA / cm. The OER catalytic performance of the electrocatalyst prepared in Comparative Example 2 is worse than that of Examples 1-3. 2The overpotential is 500 mV at a current density of 20 mA / cm. The OER catalytic performance of the electrocatalyst prepared in Comparative Example 5 is worse than that of Examples 1-3. 2 At a current density of , the overpotential is 444 mV.
[0164] Fig.28 Tafel curves of the electrocatalysts of Examples 1-3 and Comparative Examples 1-5 in alkaline electrolyte, wherein curve a is for Example 1, curve b is for Example 2, curve c is for Example 3, curve d is for Comparative Example 2, curve e is for Comparative Example 2, curve f is for Comparative Example 3, curve g is for Comparative Example 4, and curve h is for Comparative Example 5. As can be seen from the figure, the Tafel slope of commercial RuO2 in comparative example 3 is the smallest, which is 62mV / dec; the Tafel slope of Example 1 is second only to commercial RuO2, which is only 92mV / dec, indicating that the catalyst of Example 1 has higher OER kinetics; the Tafel slope of Example 2 is 109mV / dec, and the Tafel slope of Example 3 is 124mV / dec, and the Tafel slopes of both are also small, and they also have higher OER kinetics; the Tafel slope of comparative example 1 is the largest, which is 347mV / dec, and the Tafel slopes of comparative examples 2, 4 and 5 are also greater than those of Examples 1-3, which are 128mV / dec, 272mV / dec and 131mV / dec, respectively, indicating that the OER kinetics of comparative examples 1-2 and 4-5 are not as good as those of Examples 1-3.
[0165] Fig.29 CV curves of the electrocatalysts of Examples 1-3 and Comparative Examples 1-5 in the non-Faraday voltage range (0.35V-0.45V vs. Hg / HgO) in alkaline electrolyte. A linear relationship can be obtained by plotting the scan rate with half the current density difference (1 / 2Δj), and the slope is the double layer capacitance C dl . Among them, curve a is Example 1, curve b is Example 2, curve c is Example 3, curve d is Comparative Example 1, curve e is Comparative Example 2, curve f is Comparative Example 3, curve g is Comparative Example 4, and curve h is Comparative Example 5. The CV curves of each electrocatalyst present a nearly rectangular shape that is approximately symmetrical up and down. Plotting the scan rate with half the current density difference (1 / 2Δj) can obtain a linear relationship, and its slope is the double layer capacitance (C dl ), the result is as follows Fig.30 shown.
[0166] Fig.30 is the double-layer capacitance (C dl) curve graph, wherein curve a is for Example 1, curve b is for Example 2, curve c is for Example 3, curve d is for Comparative Example 1, curve e is for Comparative Example 2, curve f is for Comparative Example 3, curve g is for Comparative Example 4, and curve h is for Comparative Example 5. It can be seen from the figure that C of Examples 1-3 dl The values are relatively large, 27.72mF / cm 2 、33.47mF / cm 2 and 25.41mF / cm 2 , indicating that the heterostructure has more active sites. dl The value is 21.51mF / cm 2 , C of Comparative Example 2 dl The value is 17.85mF / cm 2 , C of Comparative Example 3 dl The value is 7.49mF / cm 2 , C of Comparative Example 4 dl The value is 2.9mF / cm 2 , C of Comparative Example 5 dl The value is 5.12mF / cm 2 , which are significantly lower than those in Examples 1-3.
[0167] Fig.31 The electrochemical impedance (EIS) curves of the electrocatalysts of Examples 1-3 and Comparative Examples 1-5 in alkaline electrolytes are shown, wherein curve a is for Example 1, curve b is for Example 2, curve c is for Example 3, curve d is for Comparative Example 1, curve e is for Comparative Example 2, curve f is for Comparative Example 3, curve g is for Comparative Example 4, and curve h is for Comparative Example 5. As can be seen from the figure, the electrochemical impedance value of Comparative Example 3 is the smallest, which is 16.8Ω; the electrochemical impedance value of Comparative Example 1 is the largest, which is 141.6Ω; the electrochemical impedance value of Comparative Example 2 is relatively small, which is 53.7Ω; the electrochemical impedance value of Comparative Example 4 is relatively large, which is 134.7Ω; the electrochemical impedance value of Comparative Example 5 is also relatively large, which is 124.7Ω; the electrochemical impedance values of Examples 1-3 are relatively small relative to Comparative Examples 1-2 and Comparative Example 4, which are 32.9Ω, 31.1Ω and 31.9Ω respectively, because the surface heterogeneous structure leads to an increase in the conductivity of the catalyst. At the same time, the electrochemical impedance values of Examples 1-3 are also smaller than that of Comparative Example 5, indicating that the three-dimensional morphology of the electrocatalyst also has an important influence on its conductivity, and the octahedral structure is more conducive to improving the conductivity.
[0168] Fig.32The constant current stability curves of the electrocatalysts of Examples 1-3 and Comparative Examples 1-5 in alkaline electrolytes are shown, wherein curve a is for Example 1, curve b is for Example 2, curve c is for Example 3, curve d is for Comparative Example 1, curve e is for Comparative Example 2, curve f is for Comparative Example 3, curve g is for Comparative Example 4, and curve h is for Comparative Example 5. As can be seen from the figure, the electrocatalysts synthesized in Examples 1-3 have excellent stability, and after 100h of testing, the voltage does not change significantly and remains stable, indicating that Examples 1-3 have long-term stability in OER; the electrocatalyst synthesized in Comparative Example 4 has the worst stability, and the voltage has been unstable in the 15h test; the electrocatalyst synthesized in Comparative Example 1 has poor stability, and the voltage has been unstable in the 26h test. The stability of the electrocatalyst synthesized in Comparative Example 2 is lower than that of Examples 1-3. After 50 hours of testing, the voltage began to become unstable; the stability of the catalyst in Comparative Example 3 is lower than that of Examples 1-3. After 50 hours of testing, the voltage began to become unstable; the stability of the electrocatalyst synthesized in Comparative Example 5 is lower than that of Examples 1-3. After 60 hours of testing, the voltage began to become unstable.
[0169] In summary, the electrocatalytic performance of the electrocatalysts prepared in Examples 1-3 is significantly better than that of Comparative Examples 1-2 and 4-5, and is not inferior to commercial RuO2 powder, and is even significantly better than RuO2 powder in terms of stability.
[0170] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a CuS@NiCo-LDHs hollow nano-octahedral heterojunction electrocatalyst, characterized in that: The following steps are involved: The Cu2O nano-octahedron is used as a hard template to undergo a precipitation conversion reaction with a soluble sulfide, and a CuS shell layer is grown on the surface of the Cu2O nano-octahedron to obtain a Cu2O@CuS nano-octahedron core-shell structure intermediate; the Cu2O@CuS nano-octahedron core-shell structure intermediate is etched with an inorganic strong acid to remove the Cu2O core to obtain a CuS hollow nano-octahedron; Heterogeneously growing a layer of NiCo-LDHs nanosheets on the surface of the CuS hollow nano-octahedron to obtain the CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalyst; The specific method of heterogeneously growing a layer of NiCo-LDHs nanosheets on the surface of the CuS hollow nano-octahedron comprises: Adding the CuS hollow nano-octahedron into the mixed solvent 2 to obtain a CuS hollow nano-octahedron suspension; Adding Ni salt, Co salt and surfactant to the CuS hollow nano-octahedron suspension, stirring evenly, then adding organic amine and organic sodium salt, stirring evenly again and heating to react, washing and drying after the reaction is completed, to obtain the CuS@NiCo-LDHs hollow nano-octahedron heterojunction electrocatalyst; The surfactant is polyvinyl pyrrolidone; the organic amine is hexamethylenetetramine; the organic sodium salt is trisodium citrate; the mass ratio of the CuS hollow nano-octahedron contained in the CuS hollow nano-octahedron suspension to the added Ni salt, Co salt, surfactant, organic amine and organic sodium salt is 0.5 ~ 1: 0.058 ~ 0.582: 0.116 ~ 1.164: 4 ~ 10: 0.7 ~ 1.4: 0.129 ~ 0.296; the reaction temperature is 80 ~ 100 ° C, and the reaction time is 4 ~ 7 h; The mixed solvent 2 is formed by mixing water and anhydrous ethanol in a volume ratio of 1:0.25 to 0.
5.
2. The preparation method according to claim 1, characterized in that The specific method of using Cu2O nano-octahedron as a hard template to react with soluble sulfide for precipitation conversion reaction comprises: Soluble sulfide is added to the Cu2O nano-octahedron suspension, and the mixture is stirred to perform a precipitation conversion reaction. After the reaction is completed, the mixture is washed and dried to obtain the Cu2O@CuS nano-octahedron core-shell structure intermediate.
3. The preparation method according to claim 2, characterized in that: The soluble sulfide is sodium sulfide or potassium sulfide; the mass ratio of the Cu2O nano-octahedron contained in the Cu2O nano-octahedron suspension to the added soluble sulfide is 1.6 to 3:0.6 to 2.0; and the time of the precipitation conversion reaction is 20 to 40 min.
4. The preparation method according to claim 1, characterized in that: The specific method of etching the Cu2O@CuS nano-octahedral core-shell structure intermediate using an inorganic strong acid comprises: The Cu2O@CuS nano octahedron core-shell structure intermediate is added into the mixed solvent 1 to obtain the Cu2O@CuS nano octahedron core-shell structure intermediate suspension; an inorganic strong acid is added into the Cu2O@CuS nano octahedron core-shell structure intermediate suspension, and the mixture is etched by stirring. After the etching is completed, the mixture is washed and dried to obtain the CuS hollow nano octahedron.
5. The preparation method according to claim 4, characterized in that: The mixed solvent 1 is formed by mixing water and anhydrous ethanol in a volume ratio of 1:0.5 to 1.5; the inorganic strong acid is hydrochloric acid, nitric acid or sulfuric acid; the mass ratio of the Cu2O@CuS nano octahedral core-shell structure intermediate contained in the Cu2O@CuS nano octahedral core-shell structure intermediate suspension to the added inorganic strong acid is 1:7 to 14.
6. The preparation method according to claim 1, characterized in that: The Ni salt is nickel sulfate, nickel nitrate or nickel chloride; the Co salt is cobalt sulfate, cobalt nitrate or cobalt chloride.
7. The preparation method according to claim 1, characterized in that: The preparation method of the Cu2O nano-octahedron comprises: A surfactant, a precipitant and a reducing agent are sequentially added to an inorganic copper salt solution, and the solution is allowed to stand for aging reaction. After the reaction is completed, the solution is washed and dried to obtain the Cu2O nano-octahedron.
8. The preparation method according to claim 7, characterized in that: The inorganic copper salt solution is a copper chloride solution, a copper sulfate solution or a copper nitrate solution; the surfactant is polyvinyl pyrrolidone; the precipitant is a strong base; the reducing agent is L-ascorbic acid; the mass ratio of the inorganic salt contained in the inorganic copper salt solution to the added surfactant, precipitant and reducing agent is 1.71 ~ 3.42: 55.56 ~ 111.12: 8 ~ 16: 8.45 ~ 16.90; the temperature of the static aging reaction is 70 ~ 100 ° C, and the time is 4 ~ 6 h.
9. A CuS@NiCo-LDHs hollow nano-octahedral heterojunction electrocatalyst prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the CuS@NiCo-LDHs hollow nano-octahedral heterojunction electrocatalyst as claimed in claim 9 in oxygen evolution in alkaline water electrolysis.